AK2 activates a novel apoptotic pathway through formation of a complex with FADD and caspase-10 - Lee, Ho-June; Pyo, Jong-Ok; Oh, Yumin; Kim, Hyo-Jin; Hong, Se-Hoon; Jeon, Young-Jun; Kim, Hyunjoo; Cho, Dong-Hyung; Woo, Ha-Na; Song, Sungmin; Nam, Jung-Hyun; Kim, Hyo Joon; et al. (NATURE PUBLISHING GROUP, 2007)
Mitochondrial proteins function as essential regulators in apoptosis. Here, we show that mitochondrial adenylate kinase 2 ( AK2) mediates mitochondrial apoptosis through the formation of an AK2-FADD-caspase-10 (AFAC10) complex. Downregulation of AK2 attenuates etoposide- or staurosporine-induced apoptosis in human cells, but not that induced by tumour-necrosis-factor-related apoptosis-inducing ligand ( TRAIL) or Fas ligand ( FasL). During intrinsic apoptosis, AK2 translocates to the cytoplasm, whereas this event is diminished in Apaf-1 knockdown cells and prevented by Bcl-2 or Bcl-X-L. Addition of purified AK2 protein to cell extracts first induces activation of caspase-10 via FADD and subsequently caspase-3 activation, but does not affect caspase-8. AFAC10 complexes are detected in cells undergoing intrinsic cell death and AK2 promotes the association of caspase-10 with FADD. In contrast, AFAC10 complexes are not detected in several etoposide-resistant human tumour cell lines. Taken together, these results suggest that, acting in concert with FADD and caspase-10, AK2 mediates a novel intrinsic apoptotic pathway that may be involved in tumorigenesis.